THE USE OF FACEBOOK GROUP DISCUSSION TO IMPROVE READING STRATEGIES: An Action Research - Endang Yuliani Rahayu (Universitas Stikubank (UNISBANK) Semarang, 2014)
The rapid development of technology influence people’s life in many aspects including the process of teaching and learning in university, school etc. Some social medias are popular in society, one of them is Facebook. This social networking can be used for any purposes Such as interacting, marketing, publishing, learning etc. The study aims to prove whether Facebook’s group discussion can be effectively used to improve reading strategies which are normally developed through classroom interaction. It is an action research design involving one group consisting of 37 students randomly sampled out from a population of 198 students. A plan-act-observe-reflect design of the study will be carried out in two cycles. Each cycle involves pretest, treatment and post test. Cycle 1 is undertaken to see if there is a significant difference between the pretest and post test upon treatment. The indicator of success of the treatment is that the post test outscores the pretest. If it does, then Cycle 2 will be conducted to convince the results. If the two cycles show an increase in the mean scores, it can be claimed that the method is effective. In other words, Facebook’s group discussion can be effectively used to improve reading strategies. Key words: Facebook group discussion, reading skill